Peak expiratory flow mediates the relationship between handgrip strength and timed up and go performance in elderly women, but not men (Clinics, 2016)
OBJECTIVE: The aim of the present study was to verify if there is sex difference in the associations among handgrip strength, peak expiratory flow (PEF) and timed up and go (TUG) test results. METHODS: The sample included 288 consecutive elderly men (n=93) and women (n=195). Functional capacity was measured using the TUG test, and muscle strength was measured based on handgrip. Moreover, as a measure of current health status, PEF was evaluated. Linear regression procedures were performed to analyze the relationships between handgrip and both PEF and TUG test results, with adjustment for confounders, and to identify the possible mediating role of PEF in the association between handgrip strength and TUG test results. RESULTS: In men, handgrip strength was associated with both PEF and TUG performance (p